Inter/Transgenerational Effects of Drugs of Abuse: A Scoping Review - Sadat-Shirazi, Mitra-Sadat; Sadeghi-Adl, Mahsa; Akbarabadi, Ardeshir; Ashabi, Ghorbangol; Mokri, Azarakhsh; Zarrindast, Mohammad-Reza (CNS & Neurological Disorders - Drug Targets, 2023)
Drug addiction is a chronic relapsing disorder that makes it a global problem. Genetics and environmental factors are the two most important factors that make someone vulnerable to drug addiction. Investigations in the past decade highlighted the role of epigenetics in the inter/transgenerational inheritance of drug addiction. A growing body of evidence showed that parental (paternal, maternal, and biparental) drug exposure before conception changes the phenotype of the offspring, which is correlated with neurochemical and neurostructural changes in the brain. The current paper reviews the effects of parental (maternal, paternal, and biparental) exposure to drugs of abuse (opioids, cocaine, nicotine, alcohol, and cannabis) before gestation in animal models.
Keywords: opioid